Sportivno-dvigatelnye testy glya otzenki spetsificeskikh koordinatsionnykh sposobnostej futbolistov - Lyakh, V. I.; Vitkovskij, Z.; Zhmuda, V. (Teorija i Praktika fiziceskoj Kul'tury, 2002)
This material is the continuation of the article "SPECIFIC COORDINATION PROPERTIES AS CRITERION OF FORECASTING OF SOCCER PLAYERS SPORT ACHIEVEMENTS" //"Theory and practice of physical culture". - 2002, ? 4, p. 21-25. It contains the detailed description of the tests and the ways of their realization. The fact sheet are included in the article on diagnostic of information parameters of coordination abilities, found also on the basis of the different criteria, and results of longitude researches about the prognosis importance of 23 parameters of coordination abilities of the soccer players who are taking place at stages of the profound training and sports perfection which were not included in the contents of the first publication.